Strategi Pengembangan Ide Dan Naskah Siaran Di Radio Sriwijaya Palembang Melalui Pendekatan Riset Program Televisi - Aldi Wijaya; Badarudin Azarkasyi (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
This study aims to analyze the process of developing broadcast ideas and scripts at Radio Sriwijaya Palembang and the application of a television program research approach to improving the quality of broadcast production. The research method used a descriptive qualitative approach through interviews, observation, and documentation. The results show that the radio creative process is still intuitive and does not yet have systematic writing standards. The television program research approach has proven relevant for strengthening the structure of ideas, script flow, and the suitability of content to audience needs. This study recommends research strategies, creative collaboration, and continuous evaluation to improve broadcast quality.